The iron hunt - Liu, Marjorie M. (Liu, Marjorie M. Hunter Kiss novel., 2008)
Maxine Kiss, the only one standing between humankind and the demons breaking out from behind prison veils, lives a life lacking in love and reveling in death, until one moment and one man changes everything.